Principles of activity of the Antimonopoly Committee of Ukraine - I. D. Kopaihora; I. I. Kopaihora (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the principles of the Antimonopoly Committee of Ukraine. The current legislation establishing the peculiarities of the implementation of the principles of activity of the Antimonopoly Committee of Ukraine is analyzed. It is established that the principles of activity of the Antimonopoly Committee of Ukraine are legality, publicity, protection of competition on the principles of equality of physical and legal persons before the law and priority of the rights of consumers. It is concluded that the principle of protection of competition on the principles of equality of individuals and legal entities before the law is the main course of practice of the Antimonopoly Committee of Ukraine.